The reaction mechanism of bovine lens leucine aminopeptidase - Schürer, Gudrun; Horn, Anselm; Gedeck, Peter; Clark, Timothy (Journal of Physical Chemistry B, 2002)
We present a quantum mechanical/molecular mechanical (QM/MM) study using the AMI Hamiltonian and a flexible MM part on the mode of action of the bovine lens leucine aminopeptidase (blLAP), a cytosolic exopeptidase that catalyzes the cleavage of the N-terminal amide bond of peptides. The reaction mechanism of this ubiquitous enzyme has not yet been clarified completely, although some suggestions based on crystallographic data have been made. One path of the several possibilities investigated was found to be clearly the most favorable and in good agreement with experimental results. Besides the elucidation of the functional roles of active-site residues, an estimation of the environment effects is given.